Frameworks for ICT policy : government, social and legal issues - Adomi, Esharenana E. (Information Science Reference, 2010)
"This book provides policy-relevant insights and information to aid those engaged in systematic research and teaching about ICT policy formation and implementation"--Provided by publisher.